Detection of Predictors of Hemorrhage in Patients with Cerebral Arteriovenous Malformation by Digital Subtraction Angiography (Bangladesh Journal of Neurosurgery, 2019)
Background: Cerebral arteriovenous malformation (AVM) is a complex tangled of dilated blood vessels in which arteries flow directly into veins without capillaries. The main cause of death in patients with cerebral AVM is intraparenchymal hemorrhage. There are multiple imaging tools that can detect the predictors of hemorrhage in cerebralarteriovenous malformation. But nowadays digital subtraction angiography (DSA) is playing a wonderful role to detect these predictors.Objectives: To detect the common predicting factors of hemorrhage from in brain by DSA. Methodology:This observational cross-sectional study was carried out in the department of Neurosurgery, Dhaka Medical College Hospital and study period was from October, 2014 to March, 2016. 76 patients of hemorrhagic stroke with clinical and radiological (CT scan) suspicion of ruptured cerebral AVM were selected by non-probability purposive sampling technique. After that enrolled patients were scrutinized according to selection criteria. Finally selected 50 patients who underwent DSA and were positive for AVM were included in this study. All the included patients’ demographic, clinical and DSA profile were recorded in pre-structured data collection sheet. All the data were compiled, edited and plotted in tabular and figure forms. Data analysis was done by chi-square test. P value was determined significant when it was